2013
DOI: 10.2217/whe.13.52
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exercise in Reducing the Risks of Gestational Diabetes Mellitus

Abstract: Women's Health (2013) 9(6), [569][570][571][572][573][574][575][576][577][578][579][580][581] support the demands of fetal growth. A progressive and marked insulin resistance develops in maternal skeletal muscle, beginning around mid-pregnancy and progressing during the third trimester to levels that approximate the insulin resistance seen in T2DM [9]. Hormones and adipo kines secreted from the placenta, including TNF-a, placental lactogen, placental growth hormone, cortisol and progesterone, are probable trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 80 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…46,[49][50][51] It remains uncertain whether adjunctive exercise, in controlling glycaemic levels in women with GDM, has the potential to reduce or delay the need for insulin therapy, which can be costly, invasive and poorly accepted by women. 45,54 This is relevant because high insulin levels, as occur in hyperglycaemia, may be associated with vascular damage; so the lower the dose of insulin required, the better. 55 In the exercise intervention groups, it was observed that there were fewer women requiring insulin (26 out of 194, 13%) compared with those receiving standard care (39 out of 190, 21%), although the meta-analysis of the studies contributing to these pooled data did not identify a statistically significant difference.…”
Section: Trialmentioning
confidence: 99%
“…46,[49][50][51] It remains uncertain whether adjunctive exercise, in controlling glycaemic levels in women with GDM, has the potential to reduce or delay the need for insulin therapy, which can be costly, invasive and poorly accepted by women. 45,54 This is relevant because high insulin levels, as occur in hyperglycaemia, may be associated with vascular damage; so the lower the dose of insulin required, the better. 55 In the exercise intervention groups, it was observed that there were fewer women requiring insulin (26 out of 194, 13%) compared with those receiving standard care (39 out of 190, 21%), although the meta-analysis of the studies contributing to these pooled data did not identify a statistically significant difference.…”
Section: Trialmentioning
confidence: 99%
“…6 Fetal concerns during a GDM pregnancy are excessive fetal growth and fetal distress that warrants suggested frequent fetal biophysical profiles and ultrasound assessments of fetal growth. 21 MNT and exercise in GDM women have been shown to lower rates of large-forgestational-age infants and macrosomia without increasing small-for-gestationalage babies. 22…”
Section: Management Of Gdmmentioning
confidence: 96%
“…Exercise is considered an adjunctive therapy for women with GDM by many professional societies 21 and is promoted in lifestyle change. 6 Despite professional endorsement there are only a few wellcontrolled studies examining the role of exercise in combination with MNT in GDM management.…”
Section: Role Of Exercise In Managing Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological and hormonal changes associated with pregnancy magnify this risk during and after pregnancy by causing an increase in adiposity and insulin resistance (Artal 2015). In pregnant women of normal body weight, physical activity reduces inflammation (Hawkins et al 2014; Wang et al 2014), as well as improves maternal insulin sensitivity (Hopkins and Artal 2013). In obese pregnant women, physical activity may decrease insulin resistance (van Poppel et al 2014).…”
Section: Introductionmentioning
confidence: 99%